Influence of applied CD34+ cell dose on the survival of Hodgkin’s lymphoma and multiple myeloma patients following autologous stem cell transplants - Todorović Balint, Milena; Bila, Jelena; Balint, Bela; Jeličić, Jelena; Djunić, Irena; Antić, Darko; Kraguljac Kurtović, Nada; Vujić, Dragana; Mihaljević, Biljana (Vojnosanitetski pregled, 2021)
Background/Aim. Autologous stem cell transplants (ASCTs) improve the rate of overall survival (OS) in patients with hematological malignancies such as multiple myeloma (MM) after induction chemotherapy, aggressive non-Hodgkin’s lymphomas (NHL), and relapsed, chemotherapy-sensitive Hodgkin’s lymphoma (HL). The study aim was to evaluate influence of applied CD34+ cell quantity on clinical outcome, as well as early post-transplant and overall survival (OS) of HL and MM patients following ASCT. Methods. This study included a total of 210 patients (90 HL/120 MM) who underwent ASCT. Stem cell (SC) mobilization was accomplished by granulocyte-colony stimulating factor (G-CSF) 10–16 μg/kg body mass (bm) following chemotherapy. For proven poor mobilizers, mobilization with G-CSF (16 μg/kgbm) and Plerixafor (24 or 48 mg) was performed. To our best knowledge, it was the first usage of the Plerixafor in our country in the ASCT-setting. Harvesting was initiated merely at "cut-off-value" of CD34+ cells ≥ 20 × 106/L in peripheral blood with "target-dose" of CD34+ cells ≥ 5 × 106/kgbm in harvest. The CD34+ cell count and viability was determined using flow cytometry. Results. The majority of HL patients (76.7%) were infused with > 5.0 × 106/kgbm CD34+ cells, while 68.3% of MM patients were treated by approximately 4.0–5.4 × 106/kgbm CD34+ dose, respectively. Beneficial response (complete/partial remission) was achieved in 83.3% (HL) and 94.2% (MM) patients. Among parameters that influenced survival of HL patients with positive response to the therapy, multivariate analysis (pre-ASCT performance status, CD34+ cell quantity applied, rapid hematopoietic, i.e. lymphocyte and platelet recovery) indicated that higher CD34+ cell dose used, along with pre-ASCT performance status correlated with superior event-free survival (EFS) and OS following ASCT. In MM patients, multivariate analysis (renal impairment, infused CD34+ cell quantity, early platelet recovery) indicated that the number of CD34+ cells infused was the most important parameter that influenced both EFS and OS after ASCT. Conclusion. Data obtained in this study undoubtedly confirmed that CD34+ cell dose applied is an independent factor that may contribute to superior clinical outcome and OS of HL and MM patients following ASCT.